A national cohort study (2000–2018) of long-term air pollution exposure and incident dementia in older adults in the United States - Liuhua Shi (Nature Portfolio, 2021)
Air pollution has been linked to neurodegenerative disease. Here the authors carried out a population-based cohort study to investigate the association between long-term exposure to PM2.5, NO2, and warm-season O3 on dementia and Alzheimer’s disease incidence in the United States.